Use of spin label EPR spectra to monitor peptide chain aggregation inside resin beads. - Cilli, Eduardo Maffud [UNESP]; Marchetto, Reinaldo [UNESP]; Schreier, S.; Nakaie, C. R. (Elsevier B.V., 1997)
An EPR approach to monitor peptide chain aggregation inside resin beads is introduced. Model low and highly peptide-loaded resins containing an aggregating sequence were labeled with a paramagnetic amino acid derivative and studied with regard to their solvation behavior in different solvent systems. For the first time in the peptide synthesis, EPR spectroscopic has allowed the detection of differentiated levels of peptide chain aggregation as a function of solvent and resin loading. (C) 1997, Elsevier B.V. Ltd. All rights reserved.